Beans - Sanders, J.H. (International Center for Tropical Agriculture, 1980)
L.A. bean production has stagnated due to the continuing yield declines. Production has been maintained by area expansion in some countries (Brazil); in others, it has increased due to a strong export demand from European and Venezuelan markets. High population and per capita income growth kept demands greater than 3 percent. As beans are grown in more marginal areas, prices and potential returns to yield-increasing technology increase. Production seems to be limited by a supply problem. Price collapse can be avoided by price floors established by the govt in good harvest yr. (CIAT)